Human rDNA and Cancer - Smirnov, Evgeny; Chmúrčiaková, Nikola; Cmarko, Dušan (Cells, 2021)
In human cells, each rDNA unit consists of the ~13 kb long ribosomal part and ~30 kb long intergenic spacer (IGS). The ribosomal part, transcribed by RNA polymerase I (pol I), includes genes coding for 18S, 5.8S, and 28S RNAs of the ribosomal particles, as well as their four transcribed spacers. Being highly repetitive, intensively transcribed, and abundantly methylated, rDNA is a very fragile site of the genome, with high risk of instability leading to cancer. Multiple small mutations, considerable expansion or contraction of the rDNA locus, and abnormally enhanced pol I transcription are usual symptoms of transformation. Recently it was found that both IGS and the ribosomal part of the locus contain many functional/potentially functional regions producing non-coding RNAs, which participate in the pol I activity regulation, stress reactions, and development of the malignant phenotype. Thus, there are solid reasons to believe that rDNA locus plays crucial role in carcinogenesis. In this review we discuss the data concerning the human rDNA and its closely associated factors as both targets and drivers of the pathways essential for carcinogenesis. We also examine whether variability in the structure of the locus may be blamed for the malignant transformation. Additionally, we consider the prospects of therapy focused on the activity of rDNA.
Keywords: RNA, Untranslated; mutace; Neoplasms; ribosomal genes; genetická variace; cancer; intergenová DNA; ribozomální DNA; human rDNA; ribozomy; nekódující RNA; Ribosomes; lidé; non-coding RNA; Humans; DNA, Intergenic; IGS; nádory; DNA, Ribosomal; Genetic Variation; Mutation; copy number